163 Assessment of the Methanogenic Archaeal Communities Throughout the Gastrointestinal Tract in Beef Cattle with Different Breeds. (21st September 2022) - Ban, Yajing; Zhou, Mi; McAllister, Tim A; Le Guan, L
Abstract: Methane mitigation in ruminants is important to reduce greenhouse gas emissions and enhance feed utilization. Methanogenic archaea inhabit the gastrointestinal tract (GIT) of ruminants where they utilize H2 reducing equivalents formed by other microbiota (i.e., bacteria, fungi, and protozoa) to reduce CO2 to methane. This study aimed to assess methanogens in the GIT of beef cattle and evaluate the influence of gut regions and cattle breeds on methanogenic ecology. Digesta were collected from six gut regions (rumen, duodenum, jejunum, ileum, colon, rectum) in forty-two beef steers representing three breeds (Angus n=13, Charolais n=14, Kinsella composite hybrid n=15). Methanogens were characterized using 16S rRNA gene amplicon sequencing with methanogen-specific primers and analyzed using RIM-DB with QIIME2. Total methanogens were quantified using qPCR with universal methanogen primers. Gut region and breed effects were assessed using the non-parametric Kruskal-Wallis test. Estimation of methanogenic populations showed a region effect (P < 0.05), with the highest copy number observed in the rumen and the lowest in the duodenum and jejunum. Ten methanogenic species were identified (with a relative abundance ≥ 0.01% in ≥ 50% of individuals per breed) throughout the GIT with Methanobrevibacter ruminantium (predominant in all regions), Methanobrevibacter gottschalkii, and Methanosphaera sp. ISO3-F5 observed in all regions and in all breeds. Divergent methanogenic compositions were observed among gut regions (P < 0.05) and breed-specific species were identified (e.g., Methanobacterium bryantii in the colon of Charolais). The alpha-diversity index (Chao1) varied among gut regions (P < 0.05), and rumen showed the highest richness over other gut regions. Breed affected the alpha-diversity where Angus was distinct from other breeds (P < 0.05). These results revealed that methanogens in the GIT are region-dependent and breed-specific, highlighting the importance of taking cattle breed and total-tract ecology into consideration to understand the role of methanogens in the GIT.